Cellulose Sulfonic Acid: An Efficient Heterogeneous Catalyst for the Synthesis of 1, 8-Dioxo-octahydroxanthenes - Hossein A. Oskooie; Leili Tahershamsi; Majid M. Heravi; Bita Baghernejad (E-Journal of Chemistry)
1,8-Dioxo-octahydroxanthenes have been synthesized good yields via a reaction of aldehydes and dimedone in the presence of cellulose sulfonic acid as a heterogeneous catalyst under solvent-free condition.